1987
DOI: 10.1507/endocrj1954.34.745
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glucose, Insulin and Glucagon Responses to Meals with Different Nutrient Compositions in Non-Insulin-Dependent Diabetes Mellitus.

Abstract: Postprandial glycaemic and hormone responses to meals with different nutrient compositions and their heterogeneity were evaluated in 16 non-insulin-dependent diabetic patients and 5 healthy volunteers. Five kinds of nutrient stimulation--75 g glucose, a Japanese mixed meal (400 kcal, carbohydrate 60%, protein 14%, fat 26%), a high protein meal (300 kcal, C 26%, P 64%, F 10%), a high fat meal (300 kcal, C 23%, P 5%, F 72%) and 20 g iv glucose--was given to each subject. On the average, in both normal and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…We show in this study that impaired secretions of both insulin and glucagon in the early phase after ingestion of glucose or mixed meal play a similarly important role in post-challenge hyperglycemia of Japanese T2DM. Previous studies have demonstrated that secretions of glucagon and insulin as well as the incretins depend on meal size and composition in healthy subjects as well as in patients with diabetes (Alsalim, Omar, Pacini, et al, 2014;Kawai, Murayama, Okuda, et al, 1987;Rijkelijkhuizen, McQuarrie, Girman, et al, 2010). We used glucose and mixed meal of fixed size and composition in the current study; it would be interesting to see if there is any difference when meal size and composition is altered.…”
Section: Discussionmentioning
confidence: 99%
“…We show in this study that impaired secretions of both insulin and glucagon in the early phase after ingestion of glucose or mixed meal play a similarly important role in post-challenge hyperglycemia of Japanese T2DM. Previous studies have demonstrated that secretions of glucagon and insulin as well as the incretins depend on meal size and composition in healthy subjects as well as in patients with diabetes (Alsalim, Omar, Pacini, et al, 2014;Kawai, Murayama, Okuda, et al, 1987;Rijkelijkhuizen, McQuarrie, Girman, et al, 2010). We used glucose and mixed meal of fixed size and composition in the current study; it would be interesting to see if there is any difference when meal size and composition is altered.…”
Section: Discussionmentioning
confidence: 99%
“…The results of measurement by R-E and E-M showed decreases in glucagon (1-29) levels with time-course after glucose loading in the NGT group, but no such changes were shown by R-M. In contrast to the participants with normal glucose tolerance, it has been reported that plasma glucagon concentration paradoxically rises after meals in patients with longstanding diabetes, and this has been supposed to be one of the causes of postprandial hyperglycemia in patients with diabetes mellitus [7][8][9][10][11] . In addition, it has been reported that intrinsic insulin secretion from pancreatic b-cells inhibits glucagon secretion from pancreatic a-cells 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the inhibition of glucagon secretion by insulin at the islet level has been investigated vigorously using animal models [41], there are several observations that insulin-induced glucagon suppression at the islet level is not always operative. For example, insulin and glucagon are both increased after mixed meal ingestion in normal subjects [42][43][44] suggesting that insulin and glucagon are regulated in more complex manner than the simple insulin-induced inhibition of glucagon. The observation that glucose induced inhibition of glucagon in diabetes subjects is observed only when glucose was introduced orally but not parenterally that has been explained by incretins [5] also suggests that insulininduced suppression of glucagon at the islet level is not necessarily operative.…”
Section: Elevated Fasting Glucagon In Subjects With Impaired Glucose mentioning
confidence: 99%